Hexavalent chromium analysis, reduction and stabilization in cement and concrete - Lokothwayo, Robson Bhekisisa (My University, 2008)
Abstract Hexavalent chromium is one of the toxic contaminants unavoidably widespread in the environment that exists in cement and concrete. Cement producers need to determine and control the content of hexavalent chromium, hence this study investigated the effect of environmental parameters on the leachability, stability and reduction of Cr(VI) in different types of concrete. Concrete cubes were made with different cement mixtures, and in some cases, reducing agents were added. The bulk and designed surface leaching experiments that simulated different environmental conditions were devised for leaching of Cr(VI). The Cr(VI) content in cement and concrete leachate solution was determined using optimized Adsorptive Stripping Voltammetry method which proved to be very sensitive and selective. Parameters like addition of MnO2, aging of concrete, increase of temperature, UV variation and decrease in pH enhanced the leachability of Cr(VI). Cement type also affected the Cr(VI) stabilization. Attempts to stabilize Cr(VI) included addition of humic acid which proved to be not effective while the addition of ferrous sulfate was successful in reducing and stabilizing Cr(VI) in concrete.